Comparison of oral hypofunction tests and determination of reference values for a subjective masticatory function test - Yoshiki Uchida; Yuji Sato; Noboru Kitagawa; Junichi Furuya; Tokiko Osawa; Akio Isobe; Mayumi Terazawa; Yukiko Hatanaka; Toshiharu Shichita (BMC, 2022)
Abstract Background In Japan, oral hypofunction has been recognized as a disease since 2018. An alternative to occlusal force testing for assessing oral hypofunction is the evaluation of the number of natural teeth. Subjective masticatory function testing, which evaluates the ease or difficulty in chewing foods, is an effective alternative to occlusal force testing. However, no reference values have been established for this test. We determined the reference values of the subjective masticatory function test and evaluated its potential as a substitute for the number of natural teeth for assessing oral hypofunction. Methods The sample consisted of 184 older adults who visited the Department of Geriatric Dentistry, Showa University Dental Hospital, from July 2018 to January 2020. The subjective masticatory function test (table for evaluation of chewing function in complete denture wearers [Chewing Score 20]) was performed using 20 foods. The occlusal force test and a receiver operating characteristic curve were used to determine the reference values for Chewing Score 20. The sensitivity, specificity, and positive and negative predictive values were calculated and compared with the occlusal force test and the number of natural teeth. Results A significant correlation (r) was found between the occlusal force test and the Chewing Score 20 (r = 0.526, p < 0.001). The reference value for Chewing Score 20 was < 85. Although the Chewing Score 20 was less sensitive than the number of natural teeth, it demonstrated a higher specificity and a positive predictive value. Conclusion Herein, a score of < 85 on the subjective masticatory function test was determined to be the optimal quantitative reference. The subjective masticatory function test may be used as an alternative for assessing oral hypofunction.